RESPON OVARIUM SAPI PERANAKAN ONGOLE DAN SAPI LIMOUSIN TERHADAP INDUKSI FOLLICLE STIMULATING HORMONE - Tanmaela, Paul B.; Manopo, Jouke H.; Lapian, Mien Th. R.; Paputungan, Umar (ZOOTEC, 2019)
OVARIAN RESPONSE OF ONGOLE CATTLE GRADE AND LIMOUSINE CATTLE BREED ON THE FOLLICLE STIMULATING HORMONEINDUCTION.Objectives of this study were to evaluate the effect of Follicle stimulating hormone (FSH) utilization and follicle wave synchronization on ovarian response and transferred embryo.This study was using secondary data of embryo products at â€œBalai Embrio Ternak Cipelang-Bogorâ€. Data were taken using types of donor female, day and date conducting super ovulation, semen code, number of corpus luteum, numbers of embryo grades (A,B,C,D), numbers of transferred embryo and numbers of unfertile ovum. This study involved Limousine and Ongle grade cattle cows experiencing in super ovulation process, with body condition scores of 3.0 to 4.0, fed grass and nutritious concentrates. The FSH was used in super ovulation by the institution called Folltropin-Vand PGF2alfa (Lutalyse). Semen was originated from bull used by the embryo transfer institution. Results showed that number of left and right luteum corpus (LC) inducing FSH were not significantly different on both cattle breeds, but number of left LC of FSH induction was significantly higher at Limousine Breed. The quality of embryo successfully transferred using FSH induction was significantly higher compared with degenerative embryo and unfertile in both cattle Breeds. The quality of degenerative embryo and unfertile egg cell was not significantly different in both breeds. Proportions of embryo successfully transferred were 85.4 percents in Ongole Grade 87.4 percents in Limousine Breed. The values of Response rateshowing comparison of female donor number responding to the number of female done of super ovulation were 100 percents. Values of recovery ratein both Breed cows showed also 100 percents.Keywords: Follicle Stimulating Hormoneinduction, ovarian response, Limousine cattle Breed, Ongole cattle Grade.